Сингулярные оптимальные управления движением ракет (обзор) - Кифоренко, Б.Н. (Прикладная механика, 2017)
Наведено аналіз сучасного стану і обговорено проблеми удосконалення методів дослідження вироджених варіаційних задач з акцентом на механіку космічного польоту. Увагу приділено дослідженню руху ракет в атмосфері. Включення до складу оптимальних траєкторій дуг сингулярного управління надає змогу в цьому випадку збільшити економічність ракетних двигунів шляхом заміни традиційних двигунів постійної тяги двигунами, що допускають дроселювання величини тяги. Наведені в огляді результати розрахунків для конкретних маневрів можуть слугувати джерелом інформації для прийняття рішень під час конструювання перспективної ракетно-космічної техніки. A review of investigations of the dynamical systems control problems is presented with emphasis on mechanics of space flight. The main attention is drawn to perfecting the methods of solving the degenerate variational problems on motion of rockets in the gravitational fields with allowance for the atmospheric resistance. These problems are immediately associated with the permanently actual problem of the practical astronautics – increasing the mass of useful load that is orbited by the carrier rockets in the circumplanetary orbits. An analysis is given for the modern approaches to solving the problems of control of rockets and spacecrafts motion over the trajectories with singular arcs that are optimal for motion of the variable mass body in the medium with resistance. The presented in this review results of some practical problems enable to estimate an advantage of using the optimal control, realization of which needs the complication of the optimal control system of the rocket engines functioning in comparison with the recent simpler laws of control.